2014
DOI: 10.1002/j.0022-0337.2014.78.3.tb05695.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Culturally Sensitive Care to Dental Students: A Multidisciplinary Approach

Abstract: Dental schools must prepare future dentists to deliver culturally sensitive care to diverse patient populations, but there is little agreement on how best to teach these skills to students. This article examines this question by exploring the historical and theoretical foundations of this area of education in dentistry, analyzes what is needed for students to learn to provide culturally sensitive care in a dental setting, and identiies the discipline-speciic skills students must master to develop this competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 27 publications
0
29
0
3
Order By: Relevance
“…Traditional curricula for dental students have a strong focus on restorative and surgical care, and it is unquestionably paramount that students acquire proficiency in clinical procedures and completion of comprehensive medical histories and physical examinations. However, equally important is being able to assess the psychosocial aspects of patients, identify various factors that contribute to oral disease, and develop tailored plans to prevent, treat, and manage oral disease 41 43 . Those studies found that students who participated in dental or non‐dental field trips to underserved communities experienced considerable professional and social transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional curricula for dental students have a strong focus on restorative and surgical care, and it is unquestionably paramount that students acquire proficiency in clinical procedures and completion of comprehensive medical histories and physical examinations. However, equally important is being able to assess the psychosocial aspects of patients, identify various factors that contribute to oral disease, and develop tailored plans to prevent, treat, and manage oral disease 41 43 . Those studies found that students who participated in dental or non‐dental field trips to underserved communities experienced considerable professional and social transformation.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a published definition of cultural competence and it is widely understood that training in cultural competence is important and necessary [2,28].Rowland et al [3] reported that, at a small number of schools (six of the thirty-four schools participating), the topic was taught in a separate course, while the majority of these schools indicated that cultural competence was presented in several different courses in the school's curriculum. Similarly, Saleh et al [4] found that the majority of dental schools presented these issues in more than one course in the curriculum, although that method of delivery was associated with less thorough coverage of the topic than was instruction at schools where there was a dedicated course for the topic.…”
Section: Discussion:-mentioning
confidence: 99%
“…Teaching culturally sensitive care is particularly difficult to implement in a dental school environment; it requires a change in perspective for both students and instructor [2].This show as that teaching cultural competency in the developing future dental professions is extremely important. [9] Conclusion:-…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding undergraduate dental curricula, efforts should focus on integrating ethical and public health concerns, both transversally and experientially (across the entire curriculum and within practicum) within a patient centered philosophy, as others [ 47 ] have advanced. In addition, interdisciplinary and reflection-based approaches to teaching may provide opportunities for critical discussion on the concepts and issues we have addressed.…”
Section: Discussionmentioning
confidence: 99%